HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN MARKETING TERHADAP KINERJA KEUANGAN PERUSAHAAN - Felicia Tanjaya; Eko Budi Santoso (Fakultas Bisnis UKDW, 2016)
This study aims to determine the role of marketing as an intervening variables in the relationshipbetween CSR and financial performance. Inconsistent result from the previous researches indicatesCSR can not directly linked with financial performance. The data used are secondary data frommining, basic industry and chemical and tobacco company's annual report during the period 2010-2014. Using path analysis with PLS, the result of this study shows that marketing as an interveningvariable mediates the relationship between CSR on financial performance in the first to the third year.Keywords: corporate social responsibility, marketing, financial performance, ROA